Perioperative Myocardial Injury/Infarction After Non-cardiac Surgery in Elderly Patients - Gao, Linggen; Chen, Lei; He, Jing; Wang, Bin; Liu, Chaoyang; Wang, Rong; Fan, Li; Cheng, Rui (Frontiers in Cardiovascular Medicine, 2022)
The number of surgical operations on elderly patients grows rapidly. Elderly surgical patients with multiple comorbidities have a higher risk of postoperative myocardial injury (PMI). PMI has been identified as cardiac troponin elevation caused by ischemia that occurs during or within 30 days after surgery with substantial short- and long-term mortality. Perioperative troponin screening is recommended in the elderly. The pathophysiology of PMI mainly results from either increased myocardial oxygen demand and/or decreased myocardial oxygen delivery. The main causes result in significant myocardial oxygen supply/demand mismatch after surgery include the pre-operative, intra-operative, and post-operative risk factors. The treatment strategy is firstly focused around the risk factors and guideline-directed medical therapy. Cardiovascular medical treatments, such as antiplatelets, β-blockers, statins, and angiotensin-converting enzyme inhibitors have shown improved outcomes in patients with PMI. The surgical risk of bleeding should be considered before using antiplatelets and anticoagulation.